Bank lending procyclicality and credit quality during financial crises - Guglielmo Maria Caporale; Stefano Di Colli; Juan Sergio Lopez (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper analyses macroeconomic and financial determinants of bad loans applying a SVAR approach to investigate whether excessive loans granted during expansionary phases can explain the more than proportional increase in non-performing loans during contractionary periods. The results indicate that the effects of a permanent shock to bad loans on the excess of credit are significant and persistent for bad loans to firms, but not for bad loans to households or in the case of Cooperative Credit Banks, who adopt more efficient lending policies.
Keywords: E44; G01; G21; C22; 330; loan losses; macroeconomic determinants; Italian banking system; SVAR